ANALYSIS OF RELATIONSHIP AMONG THE FACTORS OF NON-EXCUSABLE AFFECTING DELAY IN CONSTRUCTION PROJECT - Satrio Rekso Wilogo; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember, 2017)
The contribution of the Surabaya construction sector to the growth of the Surabaya economy over the past few decades is highly phenomenal, but many of construction projects in Surabaya are experiencing delays. While much research has been done about the cause of the delay, but the chronic problem of delay time is still very difficult to clearly discovered. The primary objectives of this research are to identify the main factors of non-excusable delay in construction projects and analyze the interdependence relationships of one factor with another. Based on literature, structural model has been developed and then use Partial Least Square to analyze the relationships with quantitative impact value among identified factors. In order to collect the data on the measured attributes, a questionnaire survey was designed in the form of an affirmative question. Respondents for this study are selected from a project manager, head project and director in the Surabaya construction firms were worked on building projects and experienced of dealling delays problem. The results of the research suggest that poor field management is one of the most significant factors significant affecting construction project delay. While path coefficient of poor capability of contractors and improper planning indicated possitive, neither of these two factors has any impact on time delay. On the other hand, poor capability of contractor to be one of the key contributing factors resulting in improper planning and improper planning affecting in poor field management.